Formation of the system of management of investment projects of reconstruction of the housing fund - Slobodeniuk , О. (Ways to Improve Construction Efficiency, 2022)
It is substantiated that the lack of a comprehensive understanding of the management of investment projects for the reconstruction of the housing stock, taking into account the domestic investment and construction complex, determines the study of this process at the system level. The specificity of systematicity is that the research is aimed at establishing the laws and mechanisms of the formation of a complex object from its component parts and identifying various types of connections in the system, as well as introducing them into a single theoretical model. The use of a system approach as a research methodology for investment design of housing reconstruction is proposed, which is based on the analysis of the object as a system and allows combining political, economic, social and other needs of the industry, taking into account the spatial characteristics of the territories. Based on the interrelationships of the main components of project management within the framework of the system approach, a structural diagram of the system of management of investment projects of housing reconstruction was developed. Such a system includes a number of elements and subsystems (information-evaluative, predictive-analytical, providing, functional-instrumental) that closely interact and logically complement each other. These elements are separate subsystems at lower hierarchical levels and have their own tasks, purposes, tools (tools, levers, technologies, methods, etc.) of managerial influence. The application of the researched theoretical and methodological foundations of the formation of the system of management of investment projects of housing reconstruction, which provide for a set of elements and interconnected subsystems, will make it possible in the future to more systematically form effective management measures to ensure this process.